Description of a new species and four newly recorded species of the genus Cosmopterix (Lepidoptera, Cosmopterigidae) from Korea - Kim, Ye-Seul; Kim, So-Yeon; Ahn, Neung-Ho; Song, Young-Gwang; Bae, Yang-Seop; Byun, Bong-Kyu (Zootaxa, 2026)
The genus Cosmopterix (Lepidoptera: Cosmopterigidae) is highly diverse, but poorly investigated in Korea. In this study, we describe one new species and four newly recorded species of Cosmopterix from Korea, based on specimens collected and re-examined from various regions during 2012 and 2024. Detailed analyses of morphology and genitalia revealed a new species, Cosmopterix ulleungensis sp. nov., along with three additional species and one subspecies newly recorded from Korea: C. oplismeniella, C. phyladelphella, C. scribaiella japonica, and C. tateshinensis. Diagnostic characters, illustrations, and distributional data for these species are provided. This study significantly expands the faunal inventory of Cosmopterix in Korea and improves the faunistic information in East Asia.